Analysis of Road Surface Deterioration Level Using Surface Distress Index and Pavement Condition Index at Jalan Rasau Jaya-Sungai Bulan - Aqila, Muzhaffar Fikri; Said, Said; Kadarini, S. Nurlaily (Fakultas Teknik Universitas Tanjungpura, 2025)
Roads are vital infrastructure that plays a role in supporting economic growth, the agricultural sector, and regional development by improving accessibility and smooth transportation. However, high traffic intensity and environmental factors can cause road quality degradation, impacting user safety and comfort. Kubu Raya Regency still faces road deterioration problems, one of which is on the Jalan Rasau Jaya - Sungai Bulan section in Rasau Jaya District. This research aims to identify the types of road deterioration, evaluate the pavement condition using the Surface Distress Index (SDI) and Pavement Condition Index (PCI) methods, and provide recommendations for improvement. The analysis showed that the road experienced various types of deterioration, including potholes, slippage cracks, ravelling, longitudinal cracking, edge cracking, transverse cracking, rutting, and alligator cracking. The SDI values at the first, second, and third kilometres were 237,5, 235, and 237,5, respectively, indicating severe deterioration. Meanwhile, the PCI values indicate poor to very poor conditions, with values of 29,91, 13,32, and 21,58. Based on the evaluation results, reconstruction is recommended for the entire segment. Both methods provide similar recommendations, but the PCI method is superior due to its more detailed classification and ability to categorize deterioration by severity and type.